2022
DOI: 10.21203/rs.3.rs-1793576/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Utilisation of modern contraceptives by sexually active adolescent girls in Rwanda: a nationwide cross-sectional study

Abstract: Background Modern contraceptive use has been shown to influence population growth, protect women’s health and rights, as well as prevent sexually transmitted infections (STIs) for barrier contraceptive methods such as condoms. The present study aimed at assessing the level of utilization and factors associated with modern contraceptive use among sexually active adolescent girls in Rwanda. Methods We used secondary data from the Rwanda Demographic and Health Survey (RDHS) 2020 data of 539 sexually active adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…However, the scientifi c literature has shown that, to some extent, teenagers use contraceptive methods after getting their fi rst birth and others acquire knowledge but lack access to contraceptives due to multifactorial reasons such as government policies, culture, and beliefs [20,21]. Additionally, even though increasing teenagers' access to contraceptives is successful in preventing unwanted pregnancies, many teenagers still lack access to a reliable source of contraceptives [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…However, the scientifi c literature has shown that, to some extent, teenagers use contraceptive methods after getting their fi rst birth and others acquire knowledge but lack access to contraceptives due to multifactorial reasons such as government policies, culture, and beliefs [20,21]. Additionally, even though increasing teenagers' access to contraceptives is successful in preventing unwanted pregnancies, many teenagers still lack access to a reliable source of contraceptives [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%